Contribution of high‐throughput DNA sequencing to the study of primary immunodeficiencies. Issue 10 (12th September 2014) - Picard, Capucine; Fischer, Alain
<x xml:space="preserve">Abstract</x> Primary immunodeficiencies (PIDs) are inborn errors of the immune system. PIDs have been characterized immunologically for the last 60 years and genetically, principally by Sanger DNA sequencing, over the last 30 years. The advent of next‐generation sequencing (NGS) in 2011, with the development of whole‐exome sequencing in particular, has facilitated the identification of previously unknown genetic lesions. NGS is rapidly generating a stream of candidate variants for an increasing number of genetically undefined PIDs. The use of NGS technology is ushering in a new era, by facilitating the discovery and characterization of new PIDs in patients with infections and other phenotypes, thereby helping to improve diagnostic accuracy. This review provides a historical overview of the identification of PIDs before NGS, and the advances and limitations of the use of NGS for the diagnosis and characterization of PIDs.